Responsible consumer behavior: Best practices and management challenges - Baltabayev, Bolat Zh; Rozhdestvenskaia, Elena M.; Krakovetskaya, Inna V.; Malanina, Veronika A. (International journal of innovative research and scientific studies)
This study investigates behavioral factors influencing responsible consumption patterns and addresses conceptual ambiguity within the theoretical framework of responsible consumption. A quantitative survey was conducted between November 2024 and February 2025 in Kazakhstan (N = 400, aged 18-66) and Russia (N = 402, aged 18-67). The questionnaire assessed participation in responsible consumption practices, consumer choice determinants, self-assessed responsibility, and willingness to change consumer behavior. Correlation and regression analyses were applied to evaluate how variables affect responsible consumption practices and cultural patterns. Results show that in Kazakhstan, 52.96% of the variance in responsible consumption engagement is explained by consumer choice, self-assessment, and readiness for behavioral change, whereas in Russia, the explained variance is 42.58%. Key drivers include consumer choice, self-perceived responsibility, and willingness to change consumer behavior, while demographic factors such as gender and age have low impact. Institutional frameworks, including fines and educational programs, also shape consumption practices differently in the two countries. The findings suggest that both individual and institutional factors contribute to the transition toward responsible consumption. Further research is required to advance responsible consumption by considering economic conditions, regulatory frameworks, and cultural norms. Such an approach will enable policymakers and businesses to apply integrated strategies that align institutional measures with individual responsibility, thereby fostering the development of an environmentally conscious society.